Assessment of Pediatric Skin Patient Satisfaction with Pharmacy Services at Basmalah Clinic Jambi - Sefiani Dwi Azmi (Journal of Pharmacopoeia, 2024)
The purpose of this study is to evaluate the level of satisfaction of pediatric skin patients with the pharmaceutical services provided at the Basmalah Jambi Clinic. The clinic is known as a primary health care provider in Jambi city and has a pharmacy unit that provides medicines for patients. Methods The research conducted was descriptive with an observational approach. The observational method is a collection technique on research subjects. The qualitative method in the study of Pediatric Satisfaction Assessment of Pharmaceutical Services at the Basmalah Jambi Clinic refers to a research approach that focuses on an in-depth understanding of patients' experiences, perceptions, and views of the pharmaceutical services they receive at the clinic. The results of this study indicate that pharmaceutical services at the Basmalah Jambi Clinic have met the needs and expectations of pediatric skin patients in general. However, there are some areas that need to be improved to enhance service quality and ensure continued patient satisfaction in the future.